Extracorporeal membrane oxygenation promotes long chain fatty acid oxidation in the immature swine heart in vivo - Kajimoto, Masaki (2013)
Extracorporeal membrane oxygenation (ECMO) supports infants and children with severe cardiopulmonary compromise. Nutritional support for these children includes provision of medium- and long-chain fatty acids (FAs). However, ECMO induces a stress response, which could limit the capacity for FA oxidation. Metabolic impairment could induce new or exacerbate existing myocardial dysfunction. Using a clinically relevant piglet model, we tested the hypothesis that ECMO maintains the myocardial capacity for FA oxidation and preserves myocardial energy state. Provision of 13-Carbon labeled medium-chain FA (octanoate), long-chain free FAs (LCFAs), and lactate into systemic circulation showed that ECMO promoted relative increases in myocardial LCFA oxidation while inhibiting lactate oxidation. Loading of these labeled substrates at high dose into the left coronary artery demonstrated metabolic flexibility as the heart preferentially oxidized octanoate. ECMO preserved this octanoate metabolic response, but also promoted LCFA oxidation and inhibited lactate utilization. Rapid upregulation of pyruvate dehydrogenase kinase-4 (PDK4) protein appeared to participate in this metabolic shift during ECMO. ECMO also increased relative flux from lactate to alanine further supporting the role for pyruvate dehydrogenase inhibition by PDK4. High dose substrate loading during ECMO also elevated the myocardial energy state indexed by phosphocreatine to ATP ratio. ECMO promotes LCFA oxidation in immature hearts, while maintaining myocardial energy state. These data support the appropriateness of FA provision during ECMO support for the immature heart.